Innovative Trends in Administrative Processes and Pedagogical Mediations in Virtual University Education as a Competitive Strategy for 2035 - Rodríguez Contreras, Gustavo; Beltrán Ladino, Sandra Milena; Sapuyes Chavez, Tania Alejandra (Universidad Francisco de Paula Santander, 2025)
The objective of the research was to analyze innovative strategic trends applicable to administrative processes and pedagogical mediations in virtual university education as competitive strategies toward 2035. The methodological design included a systematic review under the PRISMA approach, using descriptive and analytical methods. Databases such as ScienceDirect and Dimensions were consulted, employing a strategic search with terms like "Innovative Strategies," "Administrative Processes," "Pedagogical Mediations," and "Virtual University Education." Subsequently, a systematic prospective structural analysis was conducted using the MICMAC software, and an action plan was developed based on the 5W2H methodology. The results revealed that the main strategic trends identified were the use of emerging technologies such as artificial intelligence, personalized learning, the strengthening of digital competencies, and the integration of hybrid teaching models. In administrative processes, automation and the use of collaborative tools to improve interaction between students and teachers stood out. In conclusion, it was determined that innovative strategies increased efficiency in administrative and pedagogical management, in addition to enriching the educational experience of students. The importance of long-term strategic planning, focused on the continuous training of academic and administrative staff, was also highlighted to consolidate the competitiveness of virtual university education in the face of global challenges.